Cultural Contexts of the Formation of Science in the Social-Historical Context of Islamic Countries - Shamsaei, Maryam (Journal of Islamic and Social Studies, 2024)
Science has a social nature, which is formed and developed by the interaction of people in a society, and many sociological factors, including culture, are influential in its formation. This article deals with the cultural contexts of the formation of science in the social-historical framework of Islamic countries, which tries to answer the question of what place cultural factors and contexts have in the formation of science in Islamic societies. The research methodology is focused on the common paradigms in the field of the relationship between science and culture with the documentary method and logical reasoning and in the framework of the philosophy of the cultural system and has finally explained the process of how these two influence each other. The results of the study emphasize the to express the issue that science is the result of the systematic knowledge of people in every society. Science is formed and grows in the culture of societies, therefore, when a culture becomes materialistic, material sciences are inevitably formed in it with the same basis, and if it is a divine and religious culture, science is also formed on the same basis. Our definition of culture is “The set of human perceptions has reached a collective agreement ". These findings are the result of knowing the people of that society. Cognition is a tool that includes: the sense to collect information, intellect to categorize, conclude, and summarize, and heart to confirm the result. The solution for understanding science in Islam is to pay attention to the three tools of knowledge, are sense, intellect, and heart.